Promoting environmental health through information communication technologies (ICTs) to improve quality of life among Nigerians (2012)
Nigeria with a population of over 120 million people is facing numerous environmental health challenges resulting from urbanization, over population and all kinds of pollution (air, water and soil) which are some of the resultant effects of man's interaction with his environment, “environmental pollution poses a challenge to the social and economic development of the regions and communities it affects”. In other words, environmental challenges constitute a major issue that is affecting Nigeria, and the issue of concern is promoting sustainable environmental development. This paper reviews the potential environmental health risks affecting the people like air pollution due to burning of waste and poor waste disposal system, lack of access to safe drinking water, poor urban development resulting into environmental health risk practices like open defecation, lack of proper sewage disposal system and waterways contamination with organic pollutants particularly pesticides. The paper explores the potential contribution of effective communication through information and communication technologies (ICTS) in promoting safe environmental health in order to improve quality of life among Nigerians. The paper, then recommends various benefits from the dissemination of safe environmental health practices, using ICTs- based approaches to improve the quality of life among Nigerians.